The Influence of Electronic Word of Mouth (E-WOM) and Perceived Quality on the Purchasing Decisions of Xiaomi Smartphones among Students at UPN "Veteran" Jawa Timur - Rizki, Lutfi Nur; Aminah, Siti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Due to the advent of the contemporary period and the effects of globalization, smartphones are now an essential tool for people in every walk of life. Effective marketing techniques like E-Wom and Perceived quality are required to improve purchasing decisions. This study uses the Xiaomi smartphone as the research object among UPN Veteran Jawa Timur students to ascertain the impact of E-Wom and Perceived Quality on purchasing decisions. This study uses a quantitative methodology. Students at UPN Veteran Jawa Timur who own Xiaomi cellphones make up the study's population. One hundred respondents, Xiaomi smartphone users, and UPN Veteran Jawa Timur students make up the sample. Every test carried out with the SmartPLS program shows that every test satisfies the necessary threshold values, guaranteeing dependability.